2018
DOI: 10.1016/j.jenvman.2018.02.050
|View full text |Cite
|
Sign up to set email alerts
|

The construction of feelings of justice in environmental management: An empirical study of multiple biodiversity conflicts in Calakmul, Mexico

Abstract: A failure to address social concerns in biodiversity conservation can lead to feelings of injustice among some actors, and hence jeopardize conservation goals. The complex socio-cultural and political context of the Calakmul Biosphere Reserve, Mexico, has historically led to multiple biodiversity conflicts. Our goal, in this case study, was to explore perceptions of justice held by local actors in relation to biodiversity conflicts. We then aimed to determine the following: 1) people's definitions of their fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…However, this definition belies an emotional or moral choice in perspective or practice (e.g., [36]) and emphasizes the 'stake' or interest of the individual. It has been suggested that the use of the term 'actor' better acknowledges these aspects, and permits us to see research participants more widely as people [37]. Whilst in our initial study we felt it appropriate to consider the interests of 'stakeholders', in this paper we recognize that, for some individuals, interest is not dictated only by role, and we thus term those working in the field of tree health as 'actors'.…”
Section: Methodsmentioning
confidence: 99%
“…However, this definition belies an emotional or moral choice in perspective or practice (e.g., [36]) and emphasizes the 'stake' or interest of the individual. It has been suggested that the use of the term 'actor' better acknowledges these aspects, and permits us to see research participants more widely as people [37]. Whilst in our initial study we felt it appropriate to consider the interests of 'stakeholders', in this paper we recognize that, for some individuals, interest is not dictated only by role, and we thus term those working in the field of tree health as 'actors'.…”
Section: Methodsmentioning
confidence: 99%
“…obs). Despite these efforts, jaguar management is causing a latent and, at times, intense biodiversity conflict among the region's actors, leading to feelings of injustice in local populations (Lecuyer et al, 2018).…”
Section: Species Of Interest and Study Areamentioning
confidence: 99%
“…We adapted factors identified in Table 1 for the case of jaguar management (Table 2). As categorical questions might not capture the complexity of a particular situation, we asked questions based on information provided by local people in previous studies (see Lecuyer et al, 2018). Indeed, while some questions were simple to adapt, others required an understanding of the region and several iterations of pilot interviews with local actors to articulate clearly (see appendix 1).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations